Improvement of data formation in the mode of land use and land plots in the new registration forms of the state land cadastre - Kovalyshyn, O. (Land Management, Cadastre and Land Monitoring, 2017)
Adjusting of economic information and statistics to international standards leads to improvement of obtaining the data in the State Land Cadastre. In this regard, the state implemented new methodological approaches and registration forms of data acquisition.Materials for our research are the new forms of records statements, approved by Order number 337 of December 30, 2015 of the Ministry of Regional Development, Construction and Housing and Communal Services of Ukraine "On approval of new forms of administrative reports quantifying land" and instructions for filling them out.The reliability of the information provided in the process of formation and registration of land in the State Land Cadastre System in Land Register, its completeness - while holding the records of number and quality of land.According to Art. 203 of the Land Code, "Records of the number of lands - is the reflection in the statements and documents of data that characterize every land, the land areas and land structure, land distribution by owners, land users."The main objective of land records is to provide assessments of land, land tenure and land use on their actual use. That is the accumulation and systematization of information about the size, composition of land, its subspecies according to the adopted classification and economic use of land and its natural state.Along with the positive changes in the approval of new forms there are some drawbacks on their content and structural construction.Addressing these deficiencies in the structural construction of the new forms and mechanisms of formation of these improvements they enhance the reliability and transparency of obtaining credentials for the mode of land use and land in SLC. From their completeness depends the future performance of fiscal system and land use management at the local level, information provision of organizations interested in its use and regulation of land relations and land administration.Key words:StateLand Cadastre, the main, current account, accounting forms, land, land registration